Independent and combined effects of volatile organic compounds on sarcopenia: Insights into environmental pollutants and muscle health - Haobiao Liu; Zhuohang Chen; Rongqi Xiang; Yiting Liu (Ecotoxicology and Environmental Safety)
This study investigates the associations between volatile organic compound (VOC) exposure and sarcopenia, focusing on independent and combined effects and exploring potential biological mechanisms. Utilizing data from the National Health and Nutrition Examination Survey, we applied logistic regression to examine associations between individual VOCs and sarcopenia, while restricted cubic splines (RCS) assessed dose-response relationships. Weighted quantile sum (WQS) and Bayesian kernel machine regression (BKMR) evaluated mixed exposure effects. Mediation analyses explored the roles of potential mediators, alongside bioinformatic analyses to investigate the underlying mechanisms. Multivariable logistic regression identified significant associations between specific VOCs and sarcopenia, particularly for DHBMA (OR=2.71, 95 % CI: 1.62–4.55). RCS confirmed both linear and nonlinear associations of specific VOCs. WQS analysis corroborated a synergistic effect of mixed VOC exposures and increased sarcopenia risk (OR=1.64, 95 % CI: 1.14–2.36), and BKMR analysis further confirmed this positive relationship. Mediation analysis revealed that inflammation, oxidative stress, and renal function partially mediated these associations (mediated proportions: 4.67–11.00 %). Bioinformatic analyses highlighted apoptosis-related targets and pathways as key mechanisms underlying the observed associations. This study provides comprehensive evidence linking VOC exposure to sarcopenia, emphasizing the importance of reducing VOC exposure to prevent sarcopenia and associated health risks.